Research progress of estrogen receptor on prostate cancer - Gang-Lin SU; Kun HU; Jun-Wen XIAO; Yu-Chen LIU (Yixue xinzhi zazhi)
Prostate cancer is the most common malignant tumor and the second most common cause of cancer death in men. Estrogen receptors (ERs) are member of steroid hormone receptor superfamily. The role of estrogen in prostate is mainly mediated by estrogen receptor 1 (ERα) and estrogen receptor 2 (ERβ). More and more evidences suggest that estrogen receptors play an important role in the occurrence, development and prognosis of prostate cancer, and the progression of castrated resistant prostate cancer (CRPC). This article will introduce the structure and function of estrogen receptors, summarize relevant research progress in prostate cancer, analyze potential molecular mechanism and clinical application of ERs in the development of prostate cancer, and provide a new view for the treatment of prostate cancer.